The Effect of Guided Inquiry Learning Model on Students' Science Process Skills and Learning Outcomes in Physics Science Lessons - Fitriyana, Suci; Ahmad Farhan; Susanna; Abdul Hamid; Elmi Mahzum (Universitas Muhammadiyah Makassar, 2025)
Science education in the 21st century emphasizes the development of scientific competencies that integrate knowledge acquisition with science process skills (SPS), such as observing, hypothesizing, experimenting, interpreting, and communicating, which are crucial for fostering deep conceptual understanding and improving learning outcomes. However, many students remain passive learners with limited independence, particularly in rural contexts. This results in underdeveloped skills in physics and lower achievement. This study addresses this urgency by examining the effectiveness of the guided inquiry learning model in simultaneously improving SPS and learning outcomes on the topic of waves. A quasi-experimental design was applied, using a non-equivalent control group posttest-only design for SPS and a pretest–posttest control group design for learning outcomes. The sample consisted of 35 eighth-grade students from SMP Negeri 2 Kuta Baro, divided into experimental and control groups. SPS were measured through validated observation sheets, and learning outcomes were assessed using multiple-choice tests. The findings revealed that the guided inquiry group achieved significantly higher in SPS (M = 75.95) than the inquiry group (M = 70.31), with a large effect size (Cohen’s d = 0.931). Learning outcomes also improved substantially, with an N-Gain of 75.97% (high category) compared to 68.59% (moderate category) in the control group, yielding a medium effect size (d = 0.609). In conclusion, guided inquiry learning, supported by teacher scaffolding, significantly improves students’ SPS and conceptual understanding of wave phenomena. The novelty of this study lies in the simultaneous analysis of SPS and learning outcomes within one instructional framework. This study contributes to physics education by validating guided inquiry as an effective approach to foster active engagement, higher-order thinking, and meaningful learning, especially among passive learners in diverse educational contexts.